Recent advancement in conjugated polymers based photocatalytic technology for air pollutants abatement: Cases of CO2, NOx, and VOCs. (December 2022) - Ajmal, Zeeshan; Haq, Mahmood ul; Naciri, Yassine; Djellabi, Ridha; Hassan, Noor; Zaman, Shahid; Murtaza, Adil; Kumar, Anuj; Al-Sehemi, Abdullah G.; Algarni, Hamed; Al-Hartomy, Omar A.; Dong, R.; et al.
Abstract: According to World Health Organization (WHO) survey, air pollution has become the major reason of several fatal diseases, which had led to the death of 7 million peoples around the globe. The 9 people out of 10 breathe air, which exceeds WHO recommendations. Several strategies are in practice to reduce the emission of pollutants into the air, and also strict industrial, scientific, and health recommendations to use sustainable green technologies to reduce the emission of contaminants into the air. Photocatalysis technology recently has been raised as a green technology to be in practice towards the removal of air pollutants. The scientific community has passed a long pathway to develop such technology from the material, and reactor points of view. Many classes of photoactive materials have been suggested to achieve such a target. In this context, the contribution of conjugated polymers (CPs), and their modification with some common inorganic semiconductors as novel photocatalysts, has never been addressed in literature till now for said application, and is critically evaluated in this review. As we know that CPs have unique characteristics compared to inorganic semiconductors, because of their conductivity, excellent light response, good sorption ability, better redox charge generation, and separation along with a delocalized π-electrons system. The advances in photocatalytic removal/reduction of three primary air-polluting compounds such as CO2, NOX, and VOCs using CPs based photocatalysts are discussed in detail. Furthermore, the synergetic effects, obtained in CPs after combining with inorganic semiconductors are also comprehensively summarized in this review. However, such a combined system, on to better charges generation and separation, may make the Adsorb & Shuttle process into action, wherein, CPs may play the sorbing area. And, we hope that, the critical discussion on the further enhancement of photoactivity and future recommendations will open the doors for up-to-date technology transfer in modern research. Graphical abstract: Image 1 Highlights: Conjugated polymers (CPs) are excellent in all properties and generation. Herein, CO2, NOX and VOCs by CPs based photocatalysts are discussed in detail. CPs may play the sorbing area in the combined system for charges generation and separation. Critical discussion for the photoactivity and recommendations were also addressed.